2001
DOI: 10.1097/00000542-200110000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study Comparing the “Sniffing Position” with Simple Head Extension for Laryngoscopic View in Elective Surgery Patients

Abstract: Routine use of the sniffing position appears to provide no significant advantage over simple head extension for tracheal intubation in this setting. The sniffing position appears to be advantageous in obese and head extension-limited patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(110 citation statements)
references
References 14 publications
11
93
4
2
Order By: Relevance
“…In contrast to our study, Adnet et al 6 demonstrated no differences in the laryngoscopic views and intubation difficulty scale comparisons between simple head extension and sniffing positions in 456 patients. Several anatomic factors contribute to visualization of the glottis during laryngoscopy, of which OAA extension is only one addition; a difference in the OAA extension angle between simple head extension and sniffing positions was only 3.8°.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, Adnet et al 6 demonstrated no differences in the laryngoscopic views and intubation difficulty scale comparisons between simple head extension and sniffing positions in 456 patients. Several anatomic factors contribute to visualization of the glottis during laryngoscopy, of which OAA extension is only one addition; a difference in the OAA extension angle between simple head extension and sniffing positions was only 3.8°.…”
Section: Discussioncontrasting
confidence: 99%
“…They subsequently demonstrated that the sniffing position provides no advantage for improving the laryngoscopic view compared to simple head extension. 6 Direct laryngoscopy requires movement of the cervical spine for optimal visualization of the glottis. Among the cervical spine segments, extension at the occipito-atlanto-axial (OAA) complex is pivotal for several reasons.…”
mentioning
confidence: 99%
“…The results of our study were also contrary to the study done by Adnet et al 15 in 2001, where they compared the "sniffing position" with simple head extension for laryngoscopic view in elective surgery. They found no significant advantage of the sniffing position over simple head extension in terms of laryngoscopic view (with the exception of obese patients and those with limited extension).…”
Section: Jacksoncontrasting
confidence: 99%
“…For direct laryngoscopy, alignment of the oral, pharyngeal, and laryngeal axes is necessary to view the glottis, but line-of-sight visualization may be impossible for some patients secondary to anatomic factors. [4] Devices allowing the clinician to overcome these obstacles are of critical importance in airway emergencies. Studies reported improved laryngeal view with airway devices allowing for indirect visualization of the glottis in difficult airway models.…”
Section: Discussionmentioning
confidence: 99%